Special Fresno City Council Swearing-In Session in Wine Room at Valdez Hall - Watkins, Howard::::::::: (1983)
City Council Members Joe Reich, Leonel Alvarado, Joe Williams, and Mayor Daniel Whitehurst with City Clerk Jackie Ryle at microphone